Appropriate nonmycorrhizal controls in arbuscular mycorrhiza research: a microbiome perspective - Gryndler, Milan; Šmilauer, Petr; Püschel, David; Bukovská, Petra; Hršelová, Hana; Hujslová, Martina; Gryndlerová, Hana; Beskid, Olena; Konvalinková, Tereza; Jansa, Jan (Mycorrhiza, 2018)
Establishment of nonmycorrhizal controls is a "classic and recurrent theme" in mycorrhizal research. For decades, authors reported mycorrhizal plant growth/nutrition as compared to various nonmycorrhizal controls. In such studies, uncertainties remain about which nonmycorrhizal controls are most appropriate and, in particular, what effects the control inoculations have on substrate and root microbiomes. Here, different types of control and mycorrhizal inoculations were compared with respect to plant growth and nutrition, as well as the structure of root and substrate microbiomes, assessed by next-generation sequencing. We compared uninoculated ("absolute") control to inoculation with blank pot culture lacking arbuscular mycorrhizal fungi, filtrate of that blank inoculum, and filtrate of complex pot-produced mycorrhizal inoculum. Those treatments were compared to a standard mycorrhizal treatment, where the previously sterilized substrate was inoculated with complex pot-produced inoculum containing Rhizophagus irregularis SYM5. Besides this, monoxenically produced inoculum of the same fungus was applied either alone or in combination with blank inoculum. The results indicate that the presence of mycorrhizal fungus always resulted in stimulation of Andropogon gerardii plant biomass as well as in elevated phosphorus content of the plants. The microbial (bacterial and fungal) communities developing in the differently inoculated treatments, however, differed substantially from each other and no control could be obtained comparable with the treatment inoculated with complex mycorrhizal inoculum. Soil microorganisms with significant biological competences that could potentially contribute to the effects of the various inoculants on the plants were detected in roots and in plant cultivation substrate in some of the treatments.
Keywords: Pot experiment; Microbiome; Appropriate nonmycorrhizal control; Arthrobotrys; Rhizophagus irregularis; Andropogon gerardii; mikrobiota; fosfor; Andropogon; Microbiota; symbióza; biomasa; Symbiosis; Phosphorus; kořeny rostlin; Mycorrhizae; půdní mikrobiologie; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Bacteria; Biomass; Plant Roots; mykorhiza; Soil Microbiology